Study on variability of cohesive devises in idioms and Proverbs - Mardani, Tooba (LANGUAGE ART, 2022)
Cohesion as a standard textually is one of discourse analysis elements which each language has its own special pattern cohesive devices provide links between various parts of a text and dichotomized into grammatical and lexical types. This research aims to analyze comparatively English and Persian literary texts in terms of number and degree of utilization of sub-types of lexical cohesion in markers, namely; Conjunction, reference, and Collocation in proverbs and idioms. For this, first they were meticulously detected advertently in the both Persian text as a ST and English text as a TT which contrasted. The results of analysis of cohesive relations in a bilingual (English and Persian) corpus of dialogues and the findings show that there is no remarkable similarity and corresponding between them. Finally, some recommendation are made to the accuracy and neutrality of the translation texts.